Management of Tree Branch Waste into Liquid Smoke as an Agricultural Biopesticide: A Social Innovation of Pertamina EP Sangatta Field’s CSR Program - Fauziah, Elis; Pasila, Naomi Shinta; Azizah, Fitri Ulul; Dwinhoven, Ifhan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This community service activity is part of the BINTANG PERTIWI Program (Empowering Climate-Friendly and Innovative Agriculture Villages), implemented by PT Pertamina EP Sangatta Field in Pinang Raya Village, South Sangatta District, East Kutai Regency. The main challenge faced by farmers in this area is the high cost of agricultural production, largely due to their dependence on chemical fertilisers and pesticides, as well as the underutilization of abundant organic waste, particularly tree branches that are often burned, resulting in air pollution and an increased risk of land fires. The innovative solution introduced is the management of tree branch waste through a pyrolysis process to produce grade-3 liquid smoke, which is then used as an eco-friendly bio-pesticide. The activities were carried out through awareness campaigns, technical training, mentoring, and continuous monitoring and evaluation. The program results show pesticide cost savings of approximately Rp600,000 per year, improved community awareness in waste management, and strengthened farmer group capacity in adopting semi-organic farming practices. The program not only has economic benefits but also contributes to mitigating land fire risks and fostering a more sustainable environment. These findings demonstrate that social innovations based on local potential can be replicated in other regions to support sustainable agriculture. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action